A Number of Solutions to Improve the Business Efficiency of Enterprises under the Vietnam General Department of Defence Industry - Giang, Luong Hoang (International Journal of Scientific Research and Management (IJSRM), 2024)
Studying a number of solutions to improve the business efficiency of enterprises under the Vietnam General Department of Defense Industry (GDDI enterprises). The research sample is the statistics of 22 enterprises under the General Department of Defense Industry in the period from 2016 to 2021. By combining qualitative and quantitative research, the author has proposed a number of solutions to improve the efficiency of the enterprises: (i) effective use of financial leverage in GDDI enterprises, (ii) development of a strategy for loan utilization in accordance with the business strategies of GDDI enterprises, and (iii) perfection of the management apparatus.